Complications After Soft Tissue With Plate vs Bony Mandibular Reconstruction: A Systematic Review and Meta‐analysis. (25th August 2020) - Bauer, Eric; Mazul, Angela; Zenga, Joseph; Graboyes, Evan M.; Jackson, Ryan; Puram, Sidharth V.; Doering, Michelle; Pipkorn, Patrik
Abstract : Objective: Mandibular reconstruction for segmental defects is a well‐studied topic. However, there are conflicting data on the risks of delayed plate‐related complications. The objective of this systematic review and meta‐analysis was to assess long‐term plate‐related complications following reconstruction of the mandible with soft tissue and a plate as compared with immediate vascularized bony reconstruction. Data Sources: A medical librarian created search strategies with a combination of keywords and controlled vocabulary in Ovid Medline (1946–), Embase (1947–), Scopus (1960–), Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Clinicaltrials.gov. Review Methods: Candidate articles were independently reviewed by 2 authors. Inclusion/exclusion criteria were uniformly applied. Articles were considered eligible if they included adequate reporting of plate extrusion and/or fracture and had follow‐up ≥12 months. Results: A total of 2379 patients were included. The risk of plate fracture was low in cases of soft tissue with a plate (5%; 95% CI, 0.03‐0.08) and osseous reconstruction (1%). The risk of extrusion following soft tissue and plate reconstruction was 20% (95% CI, 0.15‐0.27). In the osseous reconstruction group, the risk of extrusion was 10% (95% CI, 0.06‐0.18). Revision surgery was performed twice as often following soft tissue with a plate as compared with vascularized bony reconstruction (32% [95% CI, 0.25‐0.40] vs 14% [95% CI, 0.09‐0.21], respectively). Conclusion: Delayed plate‐related complications remain a significant problem following segmental defect reconstruction. Soft tissue and plate reconstruction techniques may increase the risk of plate removal and revision surgery.